Setting the Tone of the Southern Question: Music and/as Fatalism in Italian Cinema of the Economic Miracle - Corbella, Maurizio (Journal of Film Music, 2019)
This article explores film music’s role in shaping the discourse of Italy’s questione meridionale (“Southern Question”) during the long 1960s. Part of its main argument is that music, working as a subliminal agent in film dramaturgies, impacted the perception of the Italian south on an affective, non-verbal level. It focuses on the trope of fatalism, which has often been attached to southern-ness, and examines how it was musically fleshed out in film narratives. Each of the article’s three sections tackles one specific nuance of fatalism (“sublime,” “grotesque,” and “cynical”) as it is elicited by the combination of music and the moving image. It unpacks film music’s agency by referencing topic theory and leitmotif theory, discussing film composers’ backgrounds and production practice, and tracking the historical-cultural timeliness of specific musicodramatic configurations, with reference to the Italian economic “miracle.”